Dynamic behaviour of fine recycled aggregate mortar reinforced with hybrid fibre / Mohammad Asri Abd Hamid - Abd Hamid, Mohammad Asri (2019)
The recycling of concrete waste into recycled aggregate (RA) by crushing and reprocessing concrete lumps into small particles has recently become a viable solution to the shortage of natural aggregate sources in different parts of the world. However, the inferior qualities of RAs compared with those of natural aggregates have resulted in limited commercial use of RA concrete/mortar, especially for structural application. Aggregates play a vital role in impact-resistant concrete/mortar composite because they serve as barriers to crack propagation. The low-impact strength of RAs tends to weaken the concrete/mortar at this aggregate particle when subjected with high-impact loads. In addition to safety concerns, understanding the behaviour of concrete/mortar under impact loading is important because its behaviour differs from that under quasi-static loading. This study aims to enhance the understanding of the inclusion effect of hybrid fibre on fine RA mortar (FRAM) subjected with quasi-static and high strain-rate load. Quasi-static test was conducted using an axial torsion universal testing machine, and impact load tests was applied using a 12 mm-diameter Split Hopkinson Pressure Bar (SHPB). Scanning electron microscopy (SEM) was also conducted. Two types of microfibre, namely, polypropylene and nylon, were respectively added in single and hybrid form in FRAM production, in which the number of microfibres was maintained at a volumetric fraction of 0.6%. The effects of fibres on failure mode, strain–strain curve, compressive strength and dynamic increase factor (DIF) were analysed and discussed. Experimental results showed that the hybrid fibres reinforced with FRAM exhibited large quasi-static and dynamic compressive strengths compared with those of normal mortar. The hybridisation fibre at the volume fraction of 0.3% polypropylene + 0.3% nylon (H3) yielded the most promising effective result with the improved dynamic compressive strength of FRAM with resulted higher reading for stress-strain rate average of 40 MPa. By contrast, the effect of hybrid fibre-reinforced FRAM exhibited higher DIF values than those of the reference mortar, especially under high strain-rate loading. Meanwhile, SEM observations indicated that fibre reinforcement at the microscale prohibits the initiation and growth of cracks, thus improving the impact resistance of the mortar matrix.